Career Guidance and Integration of Knowledge and Practice ——Research on the Integrated Development of Senior High School Study Tour Curriculum from the Perspective of Career Education - Dongmei Guo (Education Research on Study Tours and Practice, 2026)
As a practical medium bridging classroom learning and real society, study tour education serves as the carrier of experiential learning, while career education acts as the core value that stimulates students’ self-awareness, vocational cognition and self-driven development awareness. There exists an inherent logical compatibility between the two: study tours supply authentic scenarios and experiential venues for career education, and career education endows study tours with directional guidance and developmental value. From a principal’s perspective and grounded in school realities, this paper takes diversified industrial study tour resources covering green food, traditional brewing, high-end equipment, rail transit, military heavy industry, special materials, intelligent manufacturing and time-honored brand innovation as the research object. It systematically elaborates the theoretical logic and practical strategies of empowering the development of study tour curriculum through career education from four dimensions: integrated connotation, practical dilemmas, path construction and practical reflection. This research constructs an integrated closed-loop system covering career objectives, curriculum content, implementation paths and evaluation mechanisms, offering theoretical references and practical models for the high-quality construction of study tour curricula in general senior high schools.